Disordered eating in anorexia nervosa: give me heat, not just food - Gutierrez, Emilio; García, Naomi; Carrera, Olaia (Frontiers in Public Health, 2024)
The recommendation to apply external heat to patients with anorexia nervosa (AN) was first documented by William Gull in 1874. Gull encountered this practice during his tenure as a consultant physician, responsible for issuing medical certifications for wealthy clients seeking admission to Ticehurst Asylum, one of the most successful and reputable private asylums in England. Gull attributed the origins of this practice to the studies by Charles Chossat (1796–1875), a physiologist, physician, and politician from Geneva, who discovered the therapeutic effects of heat on starved animals by chance. In the 20th century, further evidence of the beneficial effects of heat on starved animals emerged serendipitously when anomalies were observed following a malfunction in laboratory thermostats controlling animal temperatures. Moving into the 21st century, experimental research has empirically substantiated the crucial role of ambient temperature (AT) in the animal model of activity-based anorexia (ABA). Recent translational studies have shown that a warmed environment significantly reduces anxiety around mealtime in AN patients, a method shown to be more effective than exposure-based procedures. Despite the overwhelming evidence from both animal and patient studies, it is difficult to comprehend how the impact of providing a warm environment to AN patients, particularly around mealtimes, continues to be a neglected area of research.